Strongly Coupled 3D Hybrids of N-doped Porous Carbon Nanosheet/CoNi Alloy-Encapsulated Carbon Nanotubes for Enhanced Electrocatalysis - Hou, Yang; Cui, Shumao; Wen, Zhenhai; Guo, Xiaoru; Feng, Xinliang; Chen, Junhong (Small, 2015)
A novel 3D nanoarchitecture comprising in situ-formed N-doped CoNi alloy-encapsulated carbon nanotubes (CoNi-NCNTs) grown on N-doped porous carbon nanosheets (NPCNs) is designed and constructed for both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). When evaluated as an electrocatalyst for ORR, the hybrid shows efficient catalytic activity, high selectivity, superior durability, and strong tolerance against methanol crossover compared with the commercial Pt/C catalyst. Such good oxygen reduction reaction performance is comparable to most of the previously reported results and the synergistic effect is found to boost the catalytic performance. Moreover, the constructed hybrid exhibits an excellent ORR activity with a current density of 10 mA cm-2 at 1.59 V and an onset potential of 1.57 V, even beyond the state-of-the-art Ir/C catalyst in alkaline media. The enhancement in electrochemical performance can be attributed to the unique morphology and defect structures, high porosity, good conductive networks, and strongly interacting CoNi-NCNT and NPCN in the hybrid. These results suggest the possibility for the development of effective nanocarbon electrocatalysts to replace commercial noble metal catalysts for direct use in fuel cells and water splitting devices. A novel 3D hybrid electrocatalyst consisting of N-doped CoNi alloy-encapsulated carbon nanotube (CoNi-NCNT)/N-doped porous carbon nanosheets (NPCNs) is obtained. The hybrid exhibits excellent electrocatalytic activities for the oxygen reduction and oxygen evolution reactions with good stability. The enhanced performance is correlated with the unique morphology and defect structures, high porosity, good conductive networks, and strongly interacting CoNi-NCNTs and NPCNs.
CRIS-Team Scopus Importer:2023-03-20
Keywords: hybrid materials; electrocatalysis; N doping; carbon nanotubes; carbon nanosheets; oxygen evolution reaction; oxygen reduction reaction